Population, biomass, and economic value of small ruminants in Ethiopia - Jemberu, Wudu T.; Li, Yin; Asfaw, Wondwosen; Mayberry, Dianne; Schrobback, Peggy; Rushton, Jonathan; Knight-Jones, Theodore J. D. (Frontiers in Veterinary Science, 2022)
Ethiopia has a large population of small ruminants which are mostly kept in subsistence production systems that are poorly described. Understanding production systems, their population structure, biomass, production, and economic value is essential for further analysis and effective policy making. The objective of this study was to quantify parameters for small ruminant production systems in Ethiopia to use them as a basis for analysis of disease burden within the Global Burden of Animal Diseases program. Population structure and trends of small ruminants were analyzed using data from ten annual national agriculture surveys. A stochastic herd model was used to simulate the small ruminant population, biomass, and economic value. The model was parameterized stochastically using data from statistical databases and the literature, and sensitivity analysis of main model outputs to the stochastic inputs was done. Small ruminants are held across the country mainly managed under two major production systems: the crop-livestock mixed system and the pastoral system. The small ruminant population has grown in the past ten years with an average annual growth rate of 4.6% for sheep and 6.7% for goats. The national small ruminant population for 2021 was projected at 96.4 (range 95.3 - 97.7) million heads and the mean stock biomass was about 2,129 (range 1,680 - 2,686) million kilograms. The monetary value of the small ruminant population was estimated at USD 5,953 (range 4,369-7,765) million. The annual monetary value of small ruminant production outputs was estimated at USD 1,969 (range 1, 857 – 2,857) million. Although the small ruminant population is large and rapidly growing, contributing about 2% of national annual GDP, the sub-sector is characterized by low productivity, low offtake and a limited range of production outputs with no signs of intensification. Efforts should be made to reduce small ruminant mortality, improve fertility, and better utilize products such as milk to improve the livelihoods of keepers and benefit the national economy. The approaches developed in this study can be replicated in other systems and countries to reveal trends in the size and value of livestock systems, providing a better understanding of its economic importance and performance.